Isolation of enzymatically homogeneous populations of human lymphocytes, monocytes, and granulocytes by zonal centrifugation. - Zeya, H. I. (1978)
Human monocytes, lymphocytes, granulocytes, red cells, and platelets were completely separated from each other by zonal centrifugation on linear sucrose density gradient. The monocytes contained only one tenth the amount of myeloperoxidase, one half the amount of lysozyme, one half the amount of acid ,hosphatase, and one half the amount of beta-glucuronidase found in granulocytes; the monocytes contained no alkaline phosphatase or neutral protease. The lymphocyte fraction contained only acid phosphatase and beta-glucuronidase in amounts one half as much as in the monocytes. Fluctuations in enzyme levels of monocytes and granulocytes were noted following infection. In vitro, the isolated monocytes transformed into macrophages. The results suggest that lymphocytes, monocytes, and granulocytes may be linked biochemically in a differentiation sequence through sets of commonly shared enzymes as well as by groups of enzymes specific for each divergent cell line.